2012
DOI: 10.5144/0256-4947.2012.517
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the pattern of hospital intravenous antimicrobial use in Saudi Arabia, 2006–2008

Abstract: BACKGROUND AND OBJECTIVEHospitals should measure antimicrobial use based on the WHO’s recommended metric, the defined daily dose (DDD). There is no data on antimicrobial usage based on DDD in Saudi Arabia. Thus, this study evaluates the trend in antimicrobial consumption based on this concept.DESIGN AND SETTINGObservational study in a general hospital in Saudi Arabia from 2006–2008.METHODSWe analyzed the use of intravenous systemic antibacterial agents (group J01 of the Anatomical Therapeutic Chemical [ATC] cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
1
17
1
Order By: Relevance
“…Eleven (61.1%) of these reported unwarranted and inappropriate use (typically overuse) of antimicrobials. The majority of the studies concluded that prescribing habits were to blame for the discrepancies observed, and that physicians were not prescribing according to local policies and guidelines (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Conversely, 6 (33.3%) studies reported adherence to guidelines and local institutional policies (27)(28)(29)(30)(31)(32).…”
Section: Strategies For Implementation Of Successful Antimicrobial Stmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven (61.1%) of these reported unwarranted and inappropriate use (typically overuse) of antimicrobials. The majority of the studies concluded that prescribing habits were to blame for the discrepancies observed, and that physicians were not prescribing according to local policies and guidelines (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Conversely, 6 (33.3%) studies reported adherence to guidelines and local institutional policies (27)(28)(29)(30)(31)(32).…”
Section: Strategies For Implementation Of Successful Antimicrobial Stmentioning
confidence: 99%
“…These included annual surveillance; infectious diseases team consultations (17,23,24,32) focusing on interdisciplinary collaboration; and good cross-departmental communication (22,23). In the majority of studies training of health care professionals, public health awareness and continuing medical education were considered to be important components that further enhance health care professionals' knowledge, and thus improve antibiotics use and overall prescribing appropriateness (13)(14)(15)19,21,(24)(25)(26). Others highlighted the importance of the role of the clinical pharmacist in monitoring prescriptions (i.e.…”
Section: Recommendations For Programme Development and Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…A better measure for comparing DDD with an external hospital, is the quantitative assessment of antibiotics use, with adjustment for severity of illness among hospitalized patients, using the case mix index (CMI) [11,14]. There are limited studies of antibiotic utilization in Saudi Arabia [15]. In this study, we compare the DDD, DOT, DDD per 100 bed-days, and the adjusted DDD according to CMI.…”
Section: Introductionmentioning
confidence: 99%
“…8 Several studies showed differences in types of antibiotics used in each country. [9][10][11][12][13] At best to the author's knowledge, there is no study done at KSA or Gulf and Middle East countries about antibiotics consumption in critical care services. The goal of the study is to explore the antibiotics consumption at critical care units in the Northern region (Tabuk) of the Kingdom of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%